Między etnocentryzmem a uniwersalizmem. Jak prowadzić dialog i szukać fundamentów globalnego porozumienia? - Kalbarczyk, Tomasz (Kultura-Społeczeństwo-Edukacja, 2013)
The paper refers to the discussion between different philosophical approaches to problems brought by globalisation. Building various concepts in social and political philosophy requires both rejecting radical relativism as well as finding alternatives to fundamentalism. Between radical approaches there is space for a reasonable ethics and theory of politics. I conclude with Wiktor Osiatynski’s “soft universalism” of human rights, which can be deployed as a tool for building compromise between contradictory standpoints.